2022
DOI: 10.5194/gmd-15-6259-2022
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulations with ClimateMachine v0.2.0: a new open-source code for atmospheric simulations on GPUs and CPUs

Abstract: Abstract. We introduce ClimateMachine, a new open-source atmosphere modeling framework which uses the Julia language and is designed to be scalable on central processing units (CPUs) and graphics processing units (GPUs). ClimateMachine uses a common framework both for coarser-resolution global simulations and for high-resolution, limited-area large-eddy simulations (LESs). Here, we demonstrate the LES configuration of the atmosphere model in canonical benchmark cases and atmospheric flows using a total energy-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 90 publications
4
9
0
Order By: Relevance
“…The a posteriori learning strategy clearly leads to much better scores. Topping, 2021; Ramadhan et al, 2020;Sridhar et al, 2021) naturally supports our contribution. Besides, deep differentiable emulators (Hatfield et al, 2021;Kasim et al, 2021;Nonnenmacher & Greenberg, 2021) that learn a differentiable approximation of a non-differentiable forward solver or of its adjoint may also open new avenues for the development of SGS parametrizations for state-of-the-art ESMs with a posteriori learning strategies.…”
Section: Discussionsupporting
confidence: 76%
“…The a posteriori learning strategy clearly leads to much better scores. Topping, 2021; Ramadhan et al, 2020;Sridhar et al, 2021) naturally supports our contribution. Besides, deep differentiable emulators (Hatfield et al, 2021;Kasim et al, 2021;Nonnenmacher & Greenberg, 2021) that learn a differentiable approximation of a non-differentiable forward solver or of its adjoint may also open new avenues for the development of SGS parametrizations for state-of-the-art ESMs with a posteriori learning strategies.…”
Section: Discussionsupporting
confidence: 76%
“…More specifically, St1 had an estimated top value close to 3 m 2 s −1 , whereas inner areas showed more moderate values (~1 m 2 s −1 ). Indeed, St1 is situated close to the lagoon mouth, at the ocean border, where the water flow is the most intense (the current intensity reaches peak values close to 1.5 m s −1 [27][28][29]). Applying the sensitivity analysis to the salinity showed that St1 presented the lowest sensitivity index relative to the baseline.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In the end, to close the turbulence, the so-called Reynolds-stress tensor is defined [22][23][24]. The LES is a high-resolution turbulence model sensitive to the fine details of the equations and the meshes used to represent the flow [25][26][27][28][29][30]. The SAS introduces the von Karman length scale [31][32][33] to avoid dependency determining of the RANS/LES interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We test the new implementation for both continuous and discontinuous elements (e.g., see [29] for how this can be achieved in the same source code). Other models that use either continuous or discontinuous spectral elements for atmospheric flows are, e.g., CESM2 [15], E3SM [5], both via the CAM-SE dycore [16], and ClimateMachine [30].…”
Section: Introductionmentioning
confidence: 99%